KEMAMPUAN KEPALA SEKOLAH DALAM PELAKSANAAN SUPERVISI PENGAJARAN DI SD NEGERI 24 BANDA ACEH - Rahmayanti Rahmayanti; Khairuddin Khairuddin; Nasir Usman (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2014)
Teaching supervision is one of the efforts to improve teacher professionalism. The purpose of this study was to find out how the teaching supervision program, teaching supervision techniques, and supporting and inhibiting factor of the implementation of teaching supervision of principal were. This study used descriptive method and qualitative approach. Data were collected through interview, observation and documentation study. Subject of the study were principal, vice principal and teachers. The result showed that: (1) Learning supervision program prepared by principal including planning, scheduling, supervision model, supervision clues, feedback and follow up implementation. In the implementation, principal examine learning administration instrument such as syllabus, lesson plan, teaching and learning process, annual program, semester program, effective week, question item analysis. (2) Teaching supervision techniques was conducted by class visiting, class observation, individual talk, teacher meeting, and assigning the teachers for training, upgrading, and educational seminar. (3) Supporting factor of teaching supervision implementation were teacher readiness to be coached by the principal, the establishment of good relationship in school environment, in addition the principal can monitor the teachers’ teaching development or achievement. Therefore, the principal would now which teachers were successful and which teachers needed further coaching in teaching. Meanwhile, the inhibiting factor in the implementation of teaching supervision was the limited time due to the busyness of principal inside and outside of the school.